Ontogenetic allometry in the thoracolumbar spine of mammal species with differing gait use. Issue 2 (March 2014) - Jones, Katrina E.; German, Rebecca Z.
SUMMARY Vertebrae are serially homologous structures with tight integration through their evolution and development. However, in mammals, the thoracic and lumbar regions are morphologically and functionally differentiated. We test the hypothesis that locomotor specialization is associated with altered post‐natal growth patterns in vertebrae from different vertebral regions. We use longitudinal data to examine thoracolumbar growth in two specialized half‐bounding (Oryctolagus cuniculus and Chinchilla lanigera) and two non‐specialized (Cavia porcellus and Monodelphis domestica) species with similar body sizes. Lateral X‐rays of 38 individuals were the source of centrum length, centrum height and intervertebral space length measures for 19–20 thoracolumbar vertebrae. The repeated measurements design included the same individuals soon after birth and again at adult size. Data from columns with different vertebral counts were compared by either summing (length) or averaging (height) within regions, and individual vertebrae were directly compared at the first and last five vertebral positions. Specialized half‐bounders had longer lumbar regions than generalists, which was attributable to positively allometric growth of the lumbar centra. Lumbar centrum length was more variable both ontogenetically and interspecifically than the other variables, suggesting heterochrony may be generating lumbar variation. Craniocaudal patterns of centrum growth correlate with expression of regionalizing genes (i.e., Hox).